(untitled) (Bangladesh Journal of Medical Science, 2014)
Context: In India, adolescent girls face serious health problem due to socio-economic, environmental and cultural conditions as well as gender discrimination. A vast majority of girls in India are suffering from either general or reproductive morbidities. Unhygienic practices during menstruation expose them for Reproductive Tract Infections (RTI). If not treated early, it could lead to various disabilities and consequently affect their valuable lives. This study was done with the aim of estimating the magnitude of gynaecological morbidities among unmarried adolescent girls as well as to find out the relation between menstrual hygiene and RTI. Settings and Design: Cross-Sectional Observational study conducted in two randomly selected Inter colleges (one rural and one urban) of district Dehradun, Uttarakhand state. Methods and Material: A cross-sectional study was undertaken in school going unmarried adolescent girls to know their menstrual hygiene practices as well as reproductive morbidity. Data was collected by interview method using a pretested, prestructured questionnaire after taking consent. Statistical analysis used: percentages and Chi-square test. Results: Approximately 65 % of the girls reported having dysmenorrhoea and 19 % of the girls had given the history of excessive vaginal discharge with or without low backache/lower abdominal pain. Strong association was found between Reproductive Tract Infections and poor menstrual hygiene. Conclusions: Girls should be made aware of the process of menstruation and importance of maintaining its hygiene before attaining menarche. They should also be made aware about its linkages with their forthcoming reproductive health. DOI: http://dx.doi.org/10.3329/bjms.v13i2.14257 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.170-174